TRANSYLVANIA IN THE CONTEMPORARY HUNGARIAN CINEMATOGRAPHY. THE FIGURES OF (AUTO)COLONISATION - Muga, Aleksandra (Porównania, 2013)
The Hungarian resentiments which were the result of the historic domination of the Hungarian nation over the territories of the Kingdom of Hungary before the treaty of Trianon, muted during the communist times, revived after 1989. The explosion of a painful collective memory of imperial Hungary resulted in symbolic neocolonial attempts at restoring the lost lands. The nostalgia is particularly visible in the valuative images of the Romanian Transylvania which is eagerly explored in the contemporary Hungarian cinema. The analysis of the newest films whose location was in Transylvania, is aimed at revealing the means of expression used to mentally objectify this region.